2008
DOI: 10.1007/s10964-008-9377-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Racial Discrimination and Coping Strategies on Internalizing Symptoms in African American Youth

Abstract: The current study examined the impact of racial discrimination stress on internalizing symptoms and coping strategies in a sample of 268 African American early adolescents (mean age = 12.90; 56% female) from low-income communities. Information about discrimination stress, coping, and internalizing symptoms was obtained via adolescents' self-report. It was predicted that discrimination stress would be positively associated with depression and anxiety, as well as culturally-specific coping. Finally, culturally-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(155 citation statements)
references
References 50 publications
8
143
0
4
Order By: Relevance
“…Em seguida, excluíram-se mais quatro artigos, após a leitura de seus conteúdos na ín-tegra, por não se tratarem de estudos originais ou não apresentarem medida de discriminação interpessoal autorrelatada como a principal exposição. Esse processo resultou em 34 estudos 15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35 . Adolescentes e adultos representaram a faixa etária estudada em 44% dos trabalhos (n = 12), apenas adolescentes 11% (n = 3) e crianças, adolescentes e adultos 11% (n = 3).…”
Section: Análises Estatísticasunclassified
“…Em seguida, excluíram-se mais quatro artigos, após a leitura de seus conteúdos na ín-tegra, por não se tratarem de estudos originais ou não apresentarem medida de discriminação interpessoal autorrelatada como a principal exposição. Esse processo resultou em 34 estudos 15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35 . Adolescentes e adultos representaram a faixa etária estudada em 44% dos trabalhos (n = 12), apenas adolescentes 11% (n = 3) e crianças, adolescentes e adultos 11% (n = 3).…”
Section: Análises Estatísticasunclassified
“…Nevertheless, a relatively small amount of research has examined health effects of discrimination for children and adolescents. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] This work, which has primarily focused on Black youth, has shown relationships between discrimination and greater externalizing symptoms (i.e., problem behaviors), 9,10,16,19,20 internalizing symptoms (anxiety, depression), 9,11,14,15,[21][22][23][24] and substance use. 12,13 Little is known regarding whether Latino youth similarly experience mental health deficits following discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that religious or spiritual coping may increase optimism and provide a cognitive framework for understanding stressful situations and confronting adversity 21 . Community coping moderates the association between adverse events and anxiety, but shows a negative result (increased anxiety) at high levels of discrimination and stress 16 . While it provides an explanation for re-experiencing discriminatory or co-rumination stressors, findings in Buenaventura and Quibdó confirm a positive effect and a need for the recovery of these coping strategies in Afro-Colombian communities 22 .…”
Section: Discussionmentioning
confidence: 96%
“…Afro-descendant communities of Buenaventura and Quibdó have addressed their mental health needs using ancestral wisdom and traditions. Evidence has shown that cultural beliefs, behaviors, and practices of Afro-descendants are positive in the adaptation against risk and adversity [16][17][18] . These factors reduce the risk of stress, and the literature has indicated how specific cultural factors contribute significantly to the prediction of the quality of life beyond the factors' effects (also significant) of traditional coping (active, avoidance, distraction, and seeking support) in African Americans 17 .…”
Section: Discussionmentioning
confidence: 99%